Acetabular dysplasia at the age of 1 year in children with neonatal instability of the hip: A cohort study of 243 infants. (October 2013) - Wenger, Daniel; Düppe, Henrik; Tiderius, Carl-Johan
Abstract : Background and purpose As much as one-third of all total hip arthroplasties in patients younger than 60 years may be a consequence of developmental dysplasia of the hip (DDH). Screening and early treatment of neonatal instability of the hip (NIH) reduces the incidence of DDH. We examined the radiographic outcome at 1 year in children undergoing early treatment for NIH. Subjects and methods All children born in Malmö undergo neonatal screening for NIH, and any child with suspicion of instability is referred to our clinic. We reviewed the 1-year radiographs for infants who were referred from April 2002 through December 2007. Measurements of the acetabular index at 1 year were compared between neonatally dislocated, unstable, and stable hips. Results The incidence of NIH was 7 per 1, 000 live births. The referral rate was 15 per 1, 000. 82% of those treated were girls. The mean acetabular index was higher in dislocated hips (25.3, 95% CI: 24.6–26.0) than in neonatally stable hips (22.7, 95% CI: 22.3–23.2). Girls had a higher mean acetabular index than boys and left hips had a higher mean acetabular index than right hips, which is in accordance with previous findings. Interpretation Even in children who are diagnosed and treated perinatally, radiographic differences in acetabular shape remain at 1 year. To determine whether this is of clinical importance, longer follow-up will be required.